Sequence variations in the FII, FV, F13A1, FGB and PAI-1 genes are associated with differences in myocardial perfusion. (February 2011) - Satra, Maria; Samara, Maria; Wozniak, Greta; Tzavara, Chara; Kontos, Angelos; Valotassiou, Varvara; Vamvakopoulos, Nikolaos K; Tsougos, Ioannis; Aleporou-Marinou, Vassiliki; Patrinos, George P; Kollia, Panagoula; Georgoulias, Panagiotis
Aims: Coronary artery disease (CAD) is a significant cause of morbidity and mortality in modern societies. The association between genetic markers and CAD is still poorly understood. In this study, we evaluated the effect of five genetic variants: Factor V Leiden ( FV :c.1691G>A) (rs6025), Factor II prothrombin ( FII :c.20210G>A; rs1799963), plasminogen activator inhibitor 1 ( PAI-1 ) -675(4G/5G; SERPINE1 :g.4329_4330insG; rs34857375), ββ-fibrinogen -455G>A ( FGB :c.4577G>A; rs1800790) and Factor XIII ( F13A1 :c.103G>T; rs5985) on myocardial perfusion.Materials & methods: We examined 523 patients using exercise––rest myocardial perfusion single photon emission computed tomography, where the summed stress score (SSS), summed rest score and summed difference score (SDS) indexes, were calculated. In order to examine the independent prognostic ability of genotype on SSS and SDS, multiple linear regression models were used.Results: It was found that Factor V Leiden, Factor XIII, ββ-fibrinogen and PAI-1 genotypes were independent prognostic predictors of SSS and SDS with Factor XIII exhibiting the strongest association. Moreover, Factor II prothrombin proved an independent prognostic predictor of SSS.Conclusion: Our study provides the first evidence of an association between these polymorphisms and myocardial perfusion, suggesting that the process of coronary artery disease and also patients'' prognosis, may be modified by the FV :c.1691G>A, FII :c.20210G>A, PAI-1 -675 (4G/5G), ββ-fibrinogen FGB :c.4577G>A and F13A1 :c.103G>T genotypes. Original submitted 16th August 2010; Revision submitted 1st November 2010.